Survival of the best fit: Exposure to low-wage countries and the (uneven) growth of US manufacturing plants - Andrew Barnes Bernard; J. Bradford Jensen; Peter K. Schott (Institute for Fiscal Studies (IFS), 2003)
This paper examines the role of international trade in the reallocation of U.S. manufacturing activity within and across industries from 1977 to 1997. It introduces a new measure of industry exposure to international trade, motivated by the Heckscher-Ohlin model, which focuses on where imports originate rather than their overall level. Results demonstrate that plant survival as well as output and employment growth are negatively associated with the share of industry imports sourced from the world's lowest-wage countries. Within industries, activity is reallocated towards capital-intensive plants. Plants are also more likely to alter their product mix (i.e. switch industries) in response to trade with low-wage countries. Plants altering their product mix switch to industries that are more capitaland skill-intensive.
Keywords: F11; F14; L25; L60; 330; Low-Wage Country Import Competition; Heckscher-Ohlin; Manufacturing Plant; Internationaler Wettbewerb; Verarbeitendes Gewerbe; Unternehmenswachstum; Import; Niedriglohn; USA